2007
DOI: 10.1111/j.1574-6968.2007.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Commonly usedSaccharomyces cerevisiaestrains (e.g. BY4741, W303) are growth sensitive on synthetic complete medium due to poor leucine uptake

Abstract: It is reported that some of the widely used laboratory strains of Saccharomyces cerevisiae (e.g. W303, BY4741) are sensitive to synthetic media containing all 20 amino acids [e.g. synthetic complete (SC) medium or supplemented minimal medium]. To determine the molecular basis for this unexpected sensitivity, a genomic library was screened and three genes were identified that, when overexpressed, rescue cells from this phenotype. Two of the 'rescuing' genes, BAP2 and TAT1, are related to transport of leucine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
1
35
1
1
Order By: Relevance
“…Overexpression of TAT2, encoding a high-affinity tryptophan and tyrosine permease (30), yielded yeast cells that acquired a higher tolerance toward ethanol (16). Likewise, the known growth defect of S. cerevisiae leu2 strains (e.g., BY4741) on SC media (8) could be alleviated by overexpression of TAT1 or BAP2 (both encoding amino acid permeases that transport leucine [14,30]) or by reintroducing LEU2 (8). Several studies have demonstrated that the amount of leucine provided in commonly used synthetic media is limiting for growth of leucinerequiring strains, and authors therefore recommend supplementing synthetic media with at least 400 mg leucine per liter (6,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of TAT2, encoding a high-affinity tryptophan and tyrosine permease (30), yielded yeast cells that acquired a higher tolerance toward ethanol (16). Likewise, the known growth defect of S. cerevisiae leu2 strains (e.g., BY4741) on SC media (8) could be alleviated by overexpression of TAT1 or BAP2 (both encoding amino acid permeases that transport leucine [14,30]) or by reintroducing LEU2 (8). Several studies have demonstrated that the amount of leucine provided in commonly used synthetic media is limiting for growth of leucinerequiring strains, and authors therefore recommend supplementing synthetic media with at least 400 mg leucine per liter (6,29).…”
Section: Resultsmentioning
confidence: 99%
“…BAP2 (coding for another branched-chain amino acid permease) showed a similar expression profile but was not significant at a FDR of 0.005. These three genes code for permease proteins that are able to transport leucine across the plasma membrane (14,30), and increased expression of TAT1 and BAP2 has been shown to alleviate reduced growth of BY4741 on SC media (8). A majority of the genes involved in leucine utilization and degradation show statistically significant differential expression for the SPT15-300 mutations (a genotype effect, i.e., an effect on gene expression when comparing cells expressing the SPT15-300 allele to those expressing the wildtype allele).…”
Section: Resultsmentioning
confidence: 99%
“…with an empty vector carrying the LEU2 gene (pRS315) completely abolished caffeine sensitivity. During the course of this study, it was published that laboratory yeast strains show a defect in leucine uptake that is contingent on the metabolic status of the cells (37). This led us to hypothesize that caffeine may adversely affect leucine uptake.…”
Section: Caffeine Sensitivity Of Aup1⌬ Cells Suggests Rtg Involvementmentioning
confidence: 99%
“…The fact that BY4741 is auxotrophic for leucine while FY1679-14C is not could be one of the reasons for their different behaviour. The poor growth exhibited by BY4741 in our growth conditions seems not to be attributable to the poor leucine uptake reported for this strain and other leucine auxotrophic strains (Cohen and Engelberg 2007). These authors found that growth sensitivity was only seen when BY4741 and other auxotrophic strains were grown in synthetic complete medium (SC) and not when they were grown either in SD or in YPD.…”
Section: Maximum Specific Growth Ratesmentioning
confidence: 68%